The re-emergence of emergence : the emergentist hypothesis from science to religion - Clayton, Philip, 1956-; Davies, Paul, 1962- (Oxford : Oxford University Press, 2006)
This volume introduces readers to emergence theory, outlines the major arguments in its defence, and summarizes the most powerful objections against it. It provides the clearest explication yet of this exciting new theory of science, which challenges the reductionist approach by proposing the continuous emergence of novel phenomena. - ;Much of the modern period was dominated by a r̀eductionist' theory of science. On this view, to explain any event in the world is to reduce it down to fundamental particles, laws, and forces. In recent years reductionism has been dramatically challenged by a rad.
1. Conceptual Foundations of Emergence Theory / Philip Clayton -- Part I. The Physical Sciences -- 2. The Physics of Downward Causation / Paul Davies -- 3. The Emergence of Classicality from Quantum Theory / Erich Joos -- 4. On the Nature of Emergent Reality / George F.R. Ellis -- Part II. The Biological Sciences -- 5. Emergence : The Hole at the Wheel's Hub / Terrence Deacon -- 6. The Role of Emergence in Biology / Lynn Rothschild -- 7. Emergence in Social Evolution : A Great Ape Example / Barbara Smuts -- Part III. Consciousness and Emergence -- 8. Being Realistic about Emergence / Jaegwon Kim -- 9. In Defence of Ontological Emergence and Mental Causation / Michael Silberstein -- 10. Emergence and Mental Causation / Nancey Murphy -- 11. Varieties of Emergence / David Chalmers -- Part IV. Religion and Emergence -- 12. Emergence, Mind, and Divine Action : The Hierarchy of the Sciences in Relation to the Human Mind-Brain-Body / Arthur Peacocke -- 13. Emergence : What is at Stake for Religious Reflection? / Niels Henrik Gregersen -- 14. Emergence from Quantum Physics to Religion : A Critical Appraisal / Philip Clayton.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050, 082
Keywords: Emergence (Philosophy); Science -- Philosophy; Consciousness; Religion and science; SCIENCE -- Philosophy & Social Aspects; Consciousness; Emergence (Philosophy); Religion and science; Science -- Philosophy; Electronic books